Heidegger, Philosophy, and Politics : The Heidelberg Conference - Calle-Gruber, Mireille, 1945-; Lacoue-Labarthe, Philippe; Gadamer, Hans-Georg, 1900-2002; Derrida, Jacques (Book collections on Project MUSE., 2016)
"In February of 1988, Hans-Georg Gadamer, Jacques Derrida, and Philippe Lacoue-Labarthe came together in Heidelberg before a large audience to discuss, in French, the philosophical and political implications of Martin Heidegger's thought, particularly in light of the philosopher's engagement in Nazism. This book presents a transcription and translation of their reflections and exchanges with the audience"--